Analisis tindak tutur video arab: Musalsal Fawaz wa Noura – Episode 08 – Thalabul ’Ilmi dari Channel iEN - Husna, Lativa (Maliki Interdisciplinary Journal, 2026)
This research seeks to identify the types of speech acts contained in the Arabic educational video “مسلسل فواز ونورة – الحلقة 08 – طلب العلم” uploaded on the iEN YouTube channel by applying John Searle’s speech act theory. The study is based on the growing role of YouTube as a widely used and effective educational platform, particularly among adolescents. A descriptive qualitative method with a pragmatic approach was employed to examine the utterances spoken by the characters in the video. Data were gathered through observation and note-taking techniques, while the analysis process adopted the Miles and Huberman interactive model. The results showed the presence of four categories of illocutionary speech acts, namely assertive, directive, expressive, and commissive acts, whereas declarative acts were absent. These speech acts were used not only to communicate information, but also to establish social interaction, express emotions, and convey educational as well as religious messages. The study demonstrated that Arabic educational videos on YouTube may function as an interactive and effective learning resource and contributed to the development of speech act research in digital and cross-cultural contexts.